2017
DOI: 10.1371/journal.pone.0180896
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-145 may contribute to liver fibrosis in biliary atresia by targeting ADD3

Abstract: Background and objectivesBiliary atresia (BA) is a pediatric liver disease characterized by fibro-obliteration and obstruction of the extrahepatic biliary system, that invariably leads to cirrhosis and even death, if left untreated for extended time. However, its pathology and etiology still remained unknown. In this study, we tested the expression of adducin 3 (ADD3), the gene identified as a susceptibility gene in BA by GWAS, and uncovered its upstream regulatory microRNA in the pathogenesis of BA.MethodsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
2
16
0
3
Order By: Relevance
“…A study using zebrafish model has demonstrated that the loss of add3a, but not xpnpep1 , could lead to impaired biliary function and intrahepatic defects possibly through suppressing hedgehog pathways [ 151 ]. In addition, upregulated expression of ADD3 is also reported to contribute in liver fibrosis in BA and associated with downregulation of miR-145 which targets ADD3 [ 152 ].…”
Section: Adducin and Related Disordersmentioning
confidence: 99%
“…A study using zebrafish model has demonstrated that the loss of add3a, but not xpnpep1 , could lead to impaired biliary function and intrahepatic defects possibly through suppressing hedgehog pathways [ 151 ]. In addition, upregulated expression of ADD3 is also reported to contribute in liver fibrosis in BA and associated with downregulation of miR-145 which targets ADD3 [ 152 ].…”
Section: Adducin and Related Disordersmentioning
confidence: 99%
“…When HSCs are activated, they become fibrogenic myofibroblasts and exhibit the function of fibrogenic myofibroblast-like cells, which can secrete α-smooth muscle actin (α-SMA), TIMP-1 and inhibit HSC cell apoptosis and collagen-I secretion (1315). Excessive insoluble collagen I and matrix components in the intracellular and perisinusoidal spaces can bring severe compromise to the hepatic function (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Further to these functions, recent literature has highlighted the role of adducins in T‐cell activation and stimulation of migration, with immunofluorescence techniques demonstrating migratory‐dependent localisation of adducins in CD4+ T‐cells (Butte & Thauland, ). A study by Ye et al () demonstrated the role of miRNA‐145, a regulatory miRNA, in stimulating HSC activation and proliferation via the Wnt/β‐catenin pathway and adducin‐3 (Zhou et al, ). The authors reported the differential expression of miRNA‐145 and adducin‐3 in hepatic tissues of biliary atresia samples.…”
Section: Cocaine and Adducinsmentioning
confidence: 99%
“…Further to these functions, recent literature has highlighted the role of adducins in T-cell activation and stimulation of migration, with immunofluorescence techniques demonstrating migratory-dependent localisation of adducins in CD4+ T-cells (Butte & Thauland, 2015). A study by Ye et al (2017)…”
Section: Previous Studies Have Linked Epithelial Cell Migration and Vmentioning
confidence: 99%